ASSOCIATION BETWEEN RS10735810 POLYMORPHISM OF THE VITAMIN D RECEPTOR (VDR) GENE AND THE DEVELOPMENT OF PHYSICAL QUALITIES IN UKRAINIAN ATHLETES FROM THE SUMY REGION - Biesiedina, Antonina; Harbuzova, Viktoriia; Obukhova, Olha; Oleshko, Tatyana; Demenko, Maryna (Eastern Ukrainian Medical Journal, 2025)
Introduction. Modern scientists have identified more than 25 thousand polymorphisms of the VDR gene, some of which, in particular, rs10735810, are associated with the development of physical qualities: speed and strength. Regarding the Ukrainian population, the results of the influence of the rs10735810 polymorphism on the development of speed and power qualities in track and field athletes are contradictory and ambiguous. Data on the relationship with speed and power qualities in track and field athletes are absent. Therefore, we have begun our own research to study the role of the rs10735810 polymorphism of the VDR gene in the development of speed and power qualities of track and field athletes of the Sumy region of Ukraine.Objective. The aim of the study was to study the distribution of rs10735810 polymorphic variant of the VDR gene in athletes of the Sumy region of Ukraine.Materials and methods: The buccal epithelium of 228 individuals living in the Sumy region of Ukraine was used for the study (104 athletes, including: a group of athletes with sports categories and a group of athletes with sports titles; control group – 124 individuals). Anthropometric methods were used to calculate body mass index (BMI). Genotyping of athletes and individuals of the control group for the rs10735810 polymorphism of the VDR gene was performed using polymerase chain reaction with subsequent restriction fragment length polymorphism (PCR-RFLP). Statistical analysis of the results was performed using SPSS software (version 25.0).Results. The distribution of genotypes by rs10735810-polymorphism of the VDR gene in the group of athletes was as follows: in athletes with a high rank, the ratio of homozygotes for the F-allele (F/F), heterozygotes (F/f) and homozygotes for the f-allele (f/f) is 64.28%, 14.29% and 21.43%; in the group of athletes with ranks – 47.8%, 25.5% and 26.7%; and in individuals from the control group – 27.4%, 48.4% and 24.2%, respectively. The differences in the distribution of different genotype variants in these groups are beyond statistical significance (P < 0.01). There are statistically significant differences between female and male athletes with FokI polymorphism (χ2 = 10.01; P < 0.05). The difference in the frequency of female and male individuals with the F/F genotype in the comparison groups is present (χ2 = 9.69, Р < 0.05), unlike the F/f genotype in (χ2 = 6.051; P = 7.84) and f/f genotype (χ2 = 1.263; P = 0.93). A significant effect of the FokI polymorphism of the 2nd exon of the VDR gene on the presence of sports achievements was found. The ratio of allelic variants of the VDR gene according to the FokI polymorphism (F/F, F/f, f/f) in women in the group of people with sports categories was 48.8%, 23.3% and 27.9%, while in men the corresponding indicators were 46.8%, 27.7% and 25.5%. These results indicate the presence of statistically significant differences between female and male athletes with sports categories (χ2 = 10.01; P < 0.05). In women, there are no significant differences between height, weight and BMI. As for the data in the group of men with sports categories, the following can be determined. Height and BMI indicators in both men and women with high sports achievements did not show significant differences (P > 0.05), that is, it can be concluded that the FokI VDR polymorphism does not affect height in this group of men. But if we analyze the data on body weight in the group of men, we can observe statistically significant differences (P < 0.05), which may indicate a possible influence of the FokI genotype on weight, unlike women.Conclusions. In the Sumy region of Ukraine, the F allele according to the rs10735810 polymorphism of the VDR gene in high-class athletes is dominated by individuals with the F/F genotype, and in untrained people, the heterozygous genotype – F/f – prevails. Thus, in the male group, as in the female group, a tendency can be observed that people with sports titles and ranks were more likely to have the dominant F/F genotype. When studying the ratio of individuals of different sexes with the F/F genotype in the control group, the group of individuals with sports ranks and the group of individuals with high sports ranks, statistically significant differences were found. The difference in the frequency of female and male individuals with the F/F genotype in the comparison groups is present (χ2 = 9.69, Р < 0.05). Thus, the analysis of associations of the FokI polymorphism of the VDR gene indicates that these polymorphisms indeed have a potential role in modulating physiological processes that determine the functional state of the athletes' body, which confirms our study.